Occurrence of Low Level Antibiotic Resistance and RAPD Analysis Among Escherichia coli From Catfish, and the Environments - Effareeza, Othman (Universiti Malaysia Sarawak, UNIMAS, 2010)
Escherichia coli are normal inhabitants of the gastrointestinal tract of human and animals including fish. In the present study, E. coli strains were isolated from water, sediment, and intestines of wild catfish from freshwater environment. The sampling method was carried out in three different locations; Batu 11, Matang and Samariang. Further identifications of presumptive E. coli were made by using biochemical tests, including IMViC test, oxidase test and catalase test. Sixteen isolates of presumptive E.coli tested by biochemical tests fit the E. coli profile. The 16 isolates of E. coli were characterized by antibiotic resistance profile and PCR-based DNA fingerprinting. In antibiotic susceptibility testing, the antibiotics used were ampicillin, carbenicillin, chloramphenicol, kanamycin, tetracycline and nalidixic acid. All of the E. coli isolates (100%) were susceptible to ampicillin, tetracycline and nalidixic acid, although low level of resistance (6.2%) were observed against carbenicillin, chloramphenicol and kanamycin. These results may suggest that E.coli isolates from the wild catfish and its environments were susceptible to the selected antibiotics due to the environmental factor, as wild catfish rarely being exposed to these antibiotics. Based on the DNA fingerprinting, 6 different patterns of E. coli genomes were detected. It indicates that E. coli isolated from water, sediment, and the catfish were clonally diverse and these isolates were susceptible to the commonly use antibiotics.